Adhesive chitosan-based hybrid biohydrogels for peripheral nerve injury repair - Qiu, Pengjia; Wang, Lei; Wang, Jing; Wang, Xingdong; Xu, Jianchao; An, Xiaokai; Han, Fengwang; Dong, Zhao; Zhang, Jiangtao; Shi, Peiwen; Niu, Qiang (Frontiers in Cell and Developmental Biology, 2024)
With the rapid progress of industrialization, the incidence of peripheral nerve injuries caused by trauma has been continuously increasing. These injuries result in a significant number of disabilities and irreversible functional impairments, not only severely impacting the health and quality of life of patients but also placing a heavy economic burden on families and society. Effectively promoting peripheral nerve regeneration has thus become a key focus and challenge in current research. In recent years, hybrid biohydrogels with adhesive properties have gained widespread attention due to their excellent biocompatibility, mechanical stability, conductivity, and biodegradability. These materials can provide an optimal microenvironment to promote neuron adhesion and axonal extension while offering outstanding mechanical strength to meet the fixation requirements in clinical surgeries. This paper systematically reviews the application of adhesive hybrid biohydrogels in peripheral nerve injury repair, highlighting the latest research progress in promoting nerve regeneration and improving functional recovery, and discusses the challenges and future prospects for their clinical application.